Participação dos canais de potássio no efeito relaxante do ácido ent-7a-hidroxitraquiloban-18-oico em traqueia isolada de cobaia - Martins, Italo Rossi Roseno (2012)
From Xylopia langsdorfiana A. St-Hil. & Tul. stem bark was isolated the diterpene of trachylobane class, ent-7α-hydroxytrachyloban-18-oic acid (trachylobane-318) that in previous studies showed to be able to relax guinea-pig trachea pre-contracted by carbachol (CCh). Thus, we aimed to investigate the action mechanism underlying in this trachylobane-318 relaxant activity. Trachea rings were suspended in organ baths, containing Kreb s solution, at 37 ºC and aired with carbogenic mixture. Isometric contractions were registered using a digital acquisition system. In order to evaluate a direct effect of the diterpene in Ca2+-calmodulin complex was used chlorpromazine (CPZ) (10-6 M), a calmodulin inhibitor, and we observed that trachylobane-318 relaxation effect (pD2 = 4.38 ± 0.07, n = 5) was not significantly altered in presence of this inhibitor (pD2 = 4.25 ± 0.07, n = 5). Then, was performed a protocol using different potassium (K+) extracellular concentrations which indicated that trachylobane-318 would be acting as a possible potassium channels activator since its relaxation was more potent when guinea-pig trachea was pre-contracted by KCl 18 mM (pD2 = 4.90 ± 0.25, n = 5) than by KCl 60 mM (pD2 = 3.88 ± 0.01, n = 5). To confirm the potassium channels participation was used a non-selective potassium channels blocker, tetraethylammonium (TEA+) 10 mM, that was pre-incubated before CCh addition, that resulted in an attenuation of diterpene relaxation (pD2 = 4.01 ± 0.06, n = 5). To determinate which potassium channels subtypes would be involved in the trachylobane-318 action, the diterpene relaxation curve was assessed in the presence of several potassium channels selective blockers. The fact of the trachylobane-318 relaxation curve was shifted to the right in a significant manner in the presence of 4-AP, a selective blocker of voltage activated K+ channels (Kv) (pD2 = 4.00 ± 0.06, n = 5); glibenclamide, a selective blocker of ATP-sensitive K+ channel (KATP) (pD2 = 3.91 ± 0.003, n = 5); apamin, a selective blocker of small conductance calcium-activated K+ channels (SKCa) (3.45 ± 0.14, n = 5) and big conductance calcium-activated K+ channels (BKCa) (3,80 ± 0,05, n = 5) is suggestive that the diterpene is modulating positively these channels to exert its relaxant effect. On the other hand, the inwardly rectifying K+ channels (Kir) was discarded since the relaxation curve was not altered (pD2 = 4.15 ± 0.10, n = 5) in the presence of BaCl2, selective blocker of these channels. Cyclic nucleotides participation was discarded since the relaxation curve obtained with aminophylline on guinea-pig contracted by CCh (pD2 = 4.27 ± 0.09, n = 5), a phosphodiesterases (PDEs) non-selective inhibitor, was not altered in trachylobane-318 presence (pD2 = 4.46 ± 0.08, n = 5). Thus, trachylobane-318 relaxant effect seems to involve the positive modulation of potassium channels subtypes Kv, KATP, SKCa and BKCa on guinea pig trachea.